Management of hepatic sarcoidosis - Sollors, Janina; Schlevogt, Bernhard; Schmidt, Hartmut J.; Wörns, Marcus-Alexander; Galle, Peter R.; Qian, Yuquan; Antoni, Christoph Helmer; Weis, Cleo-Aron Thias; Hetjens, Svetlana; Bergner, Raoul; Ebert, Matthias; Teufel, Andreas (Journal of gastrointestinal and liver diseases, 2022)
Background and Aims: Liver involvement in sarcoidosis may occur in up to 60% of all patients. As many patients experience only minor symptoms, a high number of undiagnosed cases must be assumed. In order to successfully identify patients with hepatic sarcoidosis, a throughout characterization of these patients and their course of disease is necessary. - Methods: We collected 40 patients from four German centers to evaluate current treatment standards and course of disease. All of our patients underwent liver biopsy with histologically proven granulomatous hepatitis. - Results: Detailed characterization of our patients showed an overall benign course of disease. Treatment was very diverse with glucocorticoids for 1 year in 55% (22/40), 5-10 years in 18% (7/40), and permanently in 18% (7/40). Other treatments included disease-modifying anti-rheumatic drugs (DMARDs), the conventional non-biological type in 53% of all patients (of these 81% received azathioprine, 46% metotrexate, 10% hydroxychloroquine, 10% mycophenolate mofetil and 10% cyclophosphamide and biologicals in 8%. Despite these very diverse treatments, patients generally showed slow progression of the disease. Two patients died. None of our patients received a liver transplantation. - Conclusions: Patients received diverse treatments and generally showed slow progression of the disease. Based on our experience, we proposed a diagnostic work up and surveillance strategy as a basis for future, prospective register studies.